Testing a new approach to translate research achievements into improved quality of care worldwide - Gagliardino, Juan Jose (2013)
The aim of the BRIDGES Research net is within the BRIDGES main scope: a) to improve the control and treatment of diabetes in a concerted effort to reduce the development and progression of chronic complications, thus decreasing the cost of its care and improving the quality of life of people with diabetes worldwide, b) to promote the early diagnosis of the disease and prevent its development, and c) to increase the critical mass of translational researchers worldwide. Better access of health providers and authorities to evidence-based practice, replicability and self-sustainability would be the central aim of this new initiative.